2021
DOI: 10.1007/s12250-021-00360-4
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of SARS-CoV-2 Induced Humoral Immune Responses in COVID-19 Patients from Hospitalization to Convalescence Over Six Months

Abstract: Understanding the persistence of antibody in convalescent COVID-19 patients may help to answer the current major concerns such as the risk of reinfection, the protection period of vaccination and the possibility of building an active herd immunity. This retrospective cohort study included 172 COVID-19 patients who were hospitalized in Wuhan. A total of 404 serum samples were obtained over six months from hospitalization to convalescence. Antibodies in the specimens were quantitatively analyzed by the capture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
(13 reference statements)
1
10
0
Order By: Relevance
“…A previous study showed that SARS‐CoV‐2 IgM peaked in the 2nd week after the onset of symptoms, and then decreased until disappeared in the 16th week after the onset of symptoms. 24 In this study, we reported that the SARS‐CoV‐2 IgM persisted positive in 12.80% convalescent COVID‐19 patients after recovery for 1 year. Not only in our study, Chuanmiao Liu and colleagues reported that 22.7% of convalescent patients still persisted as IgM antibody positive after 6 months of recovery.…”
Section: Discussionmentioning
confidence: 65%
“…A previous study showed that SARS‐CoV‐2 IgM peaked in the 2nd week after the onset of symptoms, and then decreased until disappeared in the 16th week after the onset of symptoms. 24 In this study, we reported that the SARS‐CoV‐2 IgM persisted positive in 12.80% convalescent COVID‐19 patients after recovery for 1 year. Not only in our study, Chuanmiao Liu and colleagues reported that 22.7% of convalescent patients still persisted as IgM antibody positive after 6 months of recovery.…”
Section: Discussionmentioning
confidence: 65%
“…However, the development of detectable humoral immunity is likely a predictive surrogate of protection 1,2 . The presence of broadly neutralizing serum antibodies five to eight months after SARS-CoV-2 infection have been documented by several groups [3][4][5][6][7][8][9][10] . Cases of symptomatic COVID-19 following re-infection with SARS-CoV-2 have been reported but are infrequent [11][12][13][14][15] , and recent studies have highlighted a correlation between the presence of SARS-CoV-2 antibodies and decreased risk of reinfections 16,17 .…”
Section: Introductionmentioning
confidence: 93%
“…However, there are also several reports that point to the opposite conclusion. There is compelling evidence on the persistence of robust neutralizing antibodies for months after infection, as well as favorable antibody kinetic profiles in large national studies, which range from five to eight months (72,73,91,92). To assess said establishment of a durable protection, Lumley et al studied antibody responses in healthcare workers and followed up 1265 seropositive subjects (93).…”
Section: Kineticsmentioning
confidence: 99%